Feasibility and prognostic value of adenosine stress perfusion cardiovascular magnetic resonance in patient with implantable device. (13th July 2021) - Pavon, A; Porretta, AP; Arangalage, D; Rutz, T; Hugelshofer, S; Domenichini, G; Pruvot, E; Muller, O; Monney, P; Pascale, P; Schwitter, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: stress CMR has a limited use in patients with implantable device, in order to the possible artefacts due to the metallic component and to the risk of adenosine interaction with cardiac pacing. The aim of the study was to assess the global feasibility and to assess the prognostic value of stress perfusion CMR in patients with implantable device. Materials and Methods: we conducted a retrospective single-center longitudinal analysis of consecutive patients with an implantable device referred for stress CMR, performed using a 1.5 Tesla unit (Siemens Healthcare, MAGNETOM Aera, Erlangen-Germany). Protocol was adapted according to current guidelines. Cardiac follow-up [6 months to 7 years] was obtained by medical records of direct contact with patient's cardiologist referral.  Results: 44 patients were enrolled. 34 patients needed a continuous pacing during adenosine stress, that was settled in DOO in 14 (32%) and in VOO in 20 (45%). Device integrity was not compromised by CMR and not competitive atrial or ventricular stimulation was observed during examination. Image quality was good in 95% cases. 26% cases had a perfusion deficit corresponding to a previous scar, while 12% of patients had a positive stress test. All of them needed continuous pacing during stress test and underwent to a coronary angiography who confirmed the coronary stenosis.  In patients without inducible ischemia 2 patients experienced a Non-ST-elevation Myocardial Infarction after 6 and 2 years while no other cardiac symptoms or cardiac hospitalisation was remarkable during follow up. Conclusion: adenosine stress CMR in patient who are pacemaker dependent during scanner is feasible, with an overall good image quality, proving an excellent diagnostic and prognostic value in a long term follow up even. Adenosine administration is safe and no the magnetic field interference with the correct functioning of the device have been shown in short or long term follow-up.